Going Up Inflame: Reviewing the Underexplored Role of Inflammatory Programming in Stress-Induced Intrauterine Growth Restricted Livestock - Hicks, Zena M.; Yates, Dustin T. (Frontiers in Animal Science, 2021)
The impact of intrauterine growth restriction (IUGR) on health in humans is well recognized. It is the 2nd leading cause of perinatal mortality worldwide, and it is associated with deficits in metabolism and muscle growth that increase lifelong risk for hypertension, obesity, hyperlipidemia, and type 2 diabetes. Comparatively, the barrier that IUGR imposes on livestock production is less recognized by the industry. Meat animals born with low birthweight due to IUGR are beset with greater early death loss, inefficient growth, and reduced carcass merit. These animals exhibit poor feed-to-gain ratios, less lean mass, and greater fat deposition, which increase production costs and decrease value. Ultimately, this reduces the amount of meat produced by each animal and threatens the economic sustainability of livestock industries. IUGR is most commonly the result of fetal programming responses to placental insufficiency, but the exact mechanisms by which this occurs are not well understood. In uncompromised pregnancies, inflammatory cytokines are produced at modest rates by placental and fetal tissues and play an important role in fetal development. However, unfavorable intrauterine conditions can cause cytokine activity to be excessive during critical windows of fetal development. Our recent evidence indicates that this impacts developmental programming of muscle growth and metabolism and contributes to the IUGR phenotype. In this review, we outline the role of inflammatory cytokine activity in the development of normal and IUGR phenotypes. We also highlight the contributions of sheep and other animal models in identifying mechanisms for IUGR pathologies.